Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 175305 by cortano1 last updated on 26/Aug/22

Answered by mr W last updated on 27/Aug/22

let t=(x/6)  6∫_0 ^(π/(36)) ((1−cos 2t)/(sin 3t))dt  =12∫_0 ^(π/(36)) ((sin^2  t)/(sin t (3−4 sin^2  t)))dt  =12∫_0 ^(π/(36)) ((sin t)/(4 cos^2  t−1))dt  =12∫_(π/(36)) ^0 ((d(cos t))/((2 cos t+1)(2 cos t−1)))  =12∫_(cos (π/(36))) ^1 (du/((2u+1)(2u−1)))  =6∫_(cos (π/(36))) ^1 ((du/(2u−1))−(du/(2u+1)))  =3[ln ((2u−1)/(2u+1))]_(cos (π/(36))) ^1   =3[ln (1/3)−ln ((2 cos (π/(36))−1)/(2 cos (π/(36))+1))]  =3 ln ((2 cos (π/(36))+1)/(3(2 cos (π/(36))−1)))

lett=x660π361cos2tsin3tdt=120π36sin2tsint(34sin2t)dt=120π36sint4cos2t1dt=12π360d(cost)(2cost+1)(2cost1)=12cosπ361du(2u+1)(2u1)=6cosπ361(du2u1du2u+1)=3[ln2u12u+1]cosπ361=3[ln13ln2cosπ3612cosπ36+1]=3ln2cosπ36+13(2cosπ361)

Commented by cortano1 last updated on 27/Aug/22

yes===thanks you

yes===thanksyou

Commented by Tawa11 last updated on 27/Aug/22

Great sir

Greatsir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com